Northern myths, modern identities : the nationalisation of northern mythologies since 1800 - Halink, Simon (National cultivation of culture, 2019)
This anthology of essays, Northern Myths, Modern Identities, explores the various ways in which ancient mythologies have been cultivated in the cultural construction of ethnic, national and supra-national identities from 1800 to the present. How were Old Norse, Finno-Ugric and Frisian myths employed as rhetorical devices in national narratives? And how did (and do) these new interpretations convey a sense of 'northernness'? This volume approaches these issues from an interdisciplinary and international perspective, and brings together case studies from Scandinavia, the Baltic region, Friesland, Britain, the United States and even Japan. Thus, it provides a unique insight into the reception history and uses of northern myths in the present, and their role in the creation of modern identities. Contributors are: Tim van Gerven, Gylfi Gunnlaugsson, Simon Halink, Sumarliði R. Ísleifsson, Otto S. Knottnerus, Joep Leerssen, Daisy Neijmann, Han Nijdam, Robert A. Saunders, Katja Schulz, Tom Shippey, Carline Tromp, and Kendra Willson.